M-Governance for Countering Police Corruption in Nigeria - A Phenomenological Study of the Public Complaints Rapid Response Unit's Impact on Female Complainants - Nshimbi, Christopher Changwe (University of Pretoria, 2021)
Dissertation (MA (Political Sciences))--University of Pretoria, 2021